2013
DOI: 10.3732/ajb.1200194
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers reveal a strong geographical structure in European populations of Castanea sativa (Fagaceae): Evidence for multiple glacial refugia

Abstract: The inferred population structure shows a strong geographical correspondence with the hypothesized glacial refugia and rules out the migration of the chestnut from Turkey and Greece to Italy. The homogeneous gene pool observed in Italy and Spain could have been originated from common refugia along with human-mediated colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
75
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 54 publications
16
75
1
1
Order By: Relevance
“…The loci employed in this study identified a total of 59 alleles (Table 1), with an overall richness comparable to that reported in studies covering much larger areas (Gobbin et al 2007;Wang et al 2008;Martin et al 2009;Mattioni et al 2013;Lusini et al 2014). Our marker set was highly informative for the material studied and a large proportion of alleles (61 %) was detected at a frequency below 5 %.…”
Section: Genetic Diversity In El Bierzo Orchardssupporting
confidence: 77%
See 2 more Smart Citations
“…The loci employed in this study identified a total of 59 alleles (Table 1), with an overall richness comparable to that reported in studies covering much larger areas (Gobbin et al 2007;Wang et al 2008;Martin et al 2009;Mattioni et al 2013;Lusini et al 2014). Our marker set was highly informative for the material studied and a large proportion of alleles (61 %) was detected at a frequency below 5 %.…”
Section: Genetic Diversity In El Bierzo Orchardssupporting
confidence: 77%
“…Recent studies using molecular markers have confirmed that the genetic landscape of C. sativa is complex across its distribution area-from the Atlantic Ocean to the Caspian Sea-especially in traditional nut production areas, where both grafted material and wild populations have coexisted for long periods of time (Gobbin et al 2007;Lang et al 2007;Mattioni et al 2008Mattioni et al , 2013Martin et al 2010). The northwest region of the Iberian Peninsula is particularly interesting in this context because (i) it is located at one extreme of the distribution area and concentrates the most extensive sweet chestnut stands in Spain and Portugal, (ii) it has been one of the major focal points for the native species after the last glaciation, and (iii) it has a centenary tradition of chestnut cultivation and management Ramos-Cabrer and PereiraLorenzo 2005;Pereira-Lorenzo et al 2010aMartin et al 2012;Mattioni et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These markers have proved a useful tool for determining the genetic structure in many plant species (Mattioni et al 2013, Lavor et al 2014, Noormohammadi et al 2014, Shivaprakash et al 2014. In wild Phaseolus lunatus, SSRs have been used to determine the genetic structure in populations of Costa Rica and Mexico, showing high genetic differentiation between wild populations of P. lunatus and clustering patterns based on geographical isolation and low levels of gene flow (Ouédraogo et al 2005, Martínez-Castillo et al 2006.…”
Section: K Pedro Jesús Ruiz-gil Et Almentioning
confidence: 99%
“…can be found over a wide range of climatic conditions in Europe, and its current distribution is the result of natural colonization and human intervention (Conedera et al, 2004;Mattioni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%